New temperate seaweed targets for mitigation of ruminant methane emissions: an in vitro assessment. Issue 1 (31st December 2022) - Mihaila, Alisa A.; Glasson, Christopher R. K.; Lawton, Rebecca; Muetzel, Stefan; Molano, German; Magnusson, Marie
ABSTRACT: Methane is a potent greenhouse gas with a comparatively short (9 yr) atmospheric lifetime; therefore effective strategies for methane mitigation will contribute significantly to meeting the UN Sustainable Development Goal #13 of taking rapid action against climate change. Methane emissions from enteric fermentation constitute a large proportion of agricultural greenhouse gas emissions. Low inclusions of red seaweed from the genus Asparagopsis have demonstrated near elimination of enteric methane from ruminants; however, only a limited number of other seaweeds have been assessed for their anti-methanogenic potential. New Zealand red seaweed species Bonnemaisonia hamifera, Euptilota formisissima, Plocamium cirrhosum, Vidalia colensoi, and identified aquaculture target species Ecklonia radiata and Ulva sp. B were investigated as anti-methanogenic feed additives. Seaweeds were included at 0%, 2%, 6%, or 10% of feed organic matter (OM, ryegrass hay) during in vitro fermentation assays using rumen inoculant from non-lactating Friesian x Jersey dairy cows, using Asparagopsis armata as a positive control. Total gas, methane, hydrogen, volatile fatty acids, and organic matter degradation were measured over a 48 h incubation. Inclusion of all seaweeds except Ulva sp. B reduced the production of methane at either 6 or 10% OM. Bonnemaisonia hamifera was the best performing seaweed, reducing the production of methane by 17.1%, 95.4%, and 98.8% relative to the basal feed substrate control at inclusion levels of 2%, 6%, and 10% OM, respectively, with notable increases in the production of hydrogen. Euptilota formisissima and P. cirrhosum reduced the production of methane by up to 50.5 and 39.5%, respectively, at an inclusion level of 10%, with minimal effects on measured fermentation parameters. Bromoform, the primary bioactive component in Asparagopsis, was not detected in any of the new seaweeds tested. Our results therefore identify potential alternative anti-methanogenic seaweed targets that are less susceptible to the loss of volatile bioactives during processing.